Pengelolaan Manajemen Keuangan Sekolah Pada Lembaga Pendidikan: (Studi kasus: SMK N 1 Sidikalang) - Reni situmorang; 1Hetty Saragih; Nurlela Pardede; Daniel Nababan; Oloan Simanjuntak; Tetti Manullang (edujavare, 2025)
This research explains financing and financial management activities at SMK N 1 Sidikalang. Funds are provided through School Operational Assistance (BOS), Education Development Contributions (SPP), and school entrepreneurial efforts. Financial management follows the school income and expenditure budget plan (RAPBS) with BOS funds received regularly. Planning, implementation, recording, monitoring and reporting are carried out well, although there are challenges in planning and collecting payments. Implementation of financial management takes into account the principles of transparency, accountability, effectiveness and efficiency in managing school funds. Financial management at SMK Negeri 1 Sidikalang follows the school income and expenditure budget plan (RAPBS) as well as previously allocated needs. The school treasurer of SMK N 1 Sidikalang said that the RAPBS of SMK Negeri 1 Sidikalang is periodically carried out every school year or at the beginning of the semester every six months by the principal, teachers, students, treasurer and school committee in accordance with the established budget preparation process.